KNOWLEDGE AS IMPORTANT DOMAIN IN REDUCE STIGMA AGAINST PEOPLE WITH MENTAL DISORDERS (ODGJ) - wildan Akasyah (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2020)
The negative stigma of people with mental disorder (ODGJ) has become a social phenomenon that harm sufferers. Discriminatory actions, gossip, the view that ODGJ cannot live normally, is an attitude that still maintains its negative stigma. The purpose of this study is to find a relationship between students 'and nurses' knowledge about mental health with the negative stigma that befalls ODGJ, Correlational design is used in this study. A cross-sectional research approach. Data were collected using a questionnaire, ie respondents' knowledge of ODGJ was measured by the MAKS questionnaire, and the stigma questionnaire for students and nurses (MICA). A total of 115 student and nurse respondents were sampled in this study. The sampling technique used is simple random sampling. Statistical analysis using Spearman Rank correlation test. Correlation value obtained (r) 0.02 (p <0.05). The statistical results interpret the existence of a meaningful relationship between knowledge and the formation of stigma in society. There is a relationship associated with knowledge with the formation of stigma. The knowledge contributes greatly to the formation of a positive mindset of students and nurses about ODGJ (People with Mental Disorders). The role of nurses as educators is needed to block the increasing stigma. Continuity assistance and cross-sector collaboration are needed to succeed in a stigma-free program.